The Role of Mediation in The Resolution of Civil Law Disputes in Indonesian Courts - Nurwahidah, Nurwahidah; Sanjaya, Luqman Rofiq; Ramadhan, Mohammad Zidan; Permana, Deni Yusup; Dikrurahman, Diky (Devotion : Journal of Research and Community Service, 2025)
Mediation is one of the methods of alternative dispute resolution that has been integrated into the Indonesian legal system to handle civil cases in court. Through mediation, the disputing parties can reach an agreement peacefully without having to rely on binding judges' decisions. This study aims to evaluate the role of mediation in the resolution of civil disputes in Indonesian courts, including the effectiveness, challenges, and legal implications of mediation outcomes. The study used normative legal research approach, which emphasizes the analysis of legal norms, statutory regulations, and relevant legal doctrines. The findings of the study show that mediation has the potential to speed up the dispute resolution process, save costs, reduce the burden on the court, and maintain good relations between the parties to the dispute. However, the success of mediation is influenced by a variety of factors, including the competence of the mediator, the willingness of the parties to negotiate, and the existence of supportive regulations. In the legal aspect, mediation has been regulated through Supreme Court Regulation (PERMA) Number 1 of 2016, which is a guideline for the implementation of mediation in court. This study recommends improving the quality of mediators, broader education on the benefits of mediation, and strengthening regulations to encourage the implementation of mediation as an effective dispute resolution method.